Digestive System: A Team-Based Learning Module for Histology - Kate Henkin; Keith W. Condon; James J. Brokaw (Association of American Medical Colleges, 2016)
Abstract Introduction Team-based learning (TBL) is an instructional strategy that promotes greater student engagement in the classroom. In TBL, scheduled class time is not used for lecturing. Rather, students are expected to master the basic facts and concepts of the subject matter before coming to class. Class time is devoted to applying this knowledge to solve challenging problems with students' teams. The purpose of this module is for learners to become familiarized with the digestive system. Methods The module enables students to describe the structural and functional characteristics of the digestive system, explain the cellular mechanisms responsible for maintaining the digestive system, and interpret select clinical data related to disorders of these tissues. Moreover, students will be able describe the organization and function of the oral cavity, alimentary canal, and associated organs, as well as relate the digestive system's unique structural features to its function in health and disease. This TBL module consists of four documents, including the Instructor's Guide, the Individual Readiness Assurance Test (iRAT), the Group Readiness Assurance Test (gRAT), and the Group Application Exercise. Explanations of correct answers are provided with the iRAT and Group Application Exercise documents. Prior to the TBL session, students are expected to complete the advanced preparation assignment, which consists of textbook readings and laboratory work. Results When we implemented this module with a class of 30 graduate students, the mean scores for the iRAT (93.7%), the gRAT (100%), and the clinically oriented Group Application Exercise (85.3%) reflected solid student understanding of the structure and function of the digestive system. Discussion These results show that TBL methodology is an effective strategy to teach graduate-level histology and that students do not require formal lectures to learn the material. Based on our experience, we believe that TBL offers learning outcomes comparable to lecture-based instruction but with greater clinical relevance.